Scratch-resistant plating layer of connecting terminal and electroplating method of scratch-resistant plating layer
By using a plating layer formed by composited with nano-scale hard particles on the connection terminals and adding a nickel-tungsten alloy intermediate layer, the wear and corrosion problems of a single metal plating layer are solved, achieving higher hardness, scratch resistance and service life.
Patent Information
- Application Number
- CN202411974923.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, a single metal coating is prone to wear during frequent insertion and removal or long-term use, resulting in poor contact, and is prone to rust in high humidity or corrosive gas environments, shortening its service life.
A metal substrate is used to form a plating layer by composited with nano-scale hard particles. The nanoparticles are chemically combined with the metal substrate through interfacial chemical reactions, which enhances the hardness and scratch resistance of the plating layer, and adds a nickel-tungsten alloy intermediate layer to the composite coating to improve binding force and impact resistance.
It significantly improves the hardness and scratch resistance of the coating, ensures that the coating has a long-term stable performance under high-frequency friction and high humidity environments, and extends the service life of the connection terminals.
Smart Images

Figure CN119593032A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic component surface treatment, in particular to a connection terminal scratch-resistant coating and an electroplating method thereof. Background Art
[0002] In the manufacturing process of electronic components, the surface treatment technology of the connection terminals is a key link to ensure their long-term performance and reliability. At present, the industry often uses a single metal plating (such as nickel, tin, gold, etc.) to treat the surface of the connection terminals. These metal platings have certain effects in improving conductivity and preventing oxidation, but they have limited performance in wear resistance and resistance to harsh environmental erosion, and it is difficult to meet the high requirements of modern electronic components in complex application environments.
[0003] Specifically, a single metal coating is prone to wear due to mechanical friction during frequent plugging and unplugging of the connection terminals or long-term use, resulting in poor contact and affecting the reliability of electronic equipment. In addition, in an environment with high humidity or the presence of corrosive gases, these metal coatings are also prone to oxidation or rust, further shortening the service life of the connection terminals. This phenomenon is particularly evident in electronic equipment that requires high density and long life.
[0004] In order to solve the above problems, the existing technology attempts to enhance the wear resistance and corrosion resistance of the coating by adding micron-sized hard particles to the metal coating. However, this method often has significant limitations: on the one hand, the size of the micron-sized particles is large, which easily leads to uneven distribution of the coating and destroys the overall density and surface smoothness of the coating; on the other hand, the bonding force between the micron-sized particles and the metal substrate is weak, and they are easy to fall off during long-term use, which in turn aggravates the performance degradation of the coating. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a scratch-resistant coating for a connection terminal and an electroplating method thereof, which solves the problem that a single metal coating is easily worn out during frequent plugging and unplugging or long-term use, resulting in poor contact, and is easily corroded and has a shortened service life in a high humidity or corrosive gas environment. At the same time, the present invention overcomes the problems of uneven coating distribution, decreased density, and easy shedding of particles caused by adding micron-sized hard particles in the prior art.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a scratch-resistant coating for a connecting terminal, the coating comprising a metal substrate and nano-scale hard particles distributed therein, the nano-scale hard particles being combined with the metal substrate through an interfacial chemical reaction.
[0007] The metal substrate is the main carrier of the electronic connection terminal, providing basic mechanical support and conductive properties. By selecting highly conductive metals such as copper or copper alloy as the substrate, the electrical properties of the connection terminal can be guaranteed. Nano-scale hard particles (such as silicon carbide, boron nitride, zirconium oxide) are embedded in the metal substrate through interfacial chemical reactions to form a composite structure. The essence of interfacial chemical reactions is that the active sites on the particle surface (such as hydroxyl or amino groups) undergo chemical adsorption or chemical bond formation with the surface of the metal substrate, thereby improving the bonding strength. The embedding of nanoparticles enhances the hardness (microhardness HV>1000) and scratch resistance of the coating. At the same time, interfacial chemical bonding ensures that the coating does not fall off under high-intensity friction environments.
[0008] Preferably, the nano-scale hard particles include one or more of silicon carbide, boron nitride and zirconium oxide, and the mass percentage is 1-5%.
[0009] Particle type selection: Silicon carbide (SiC) has high hardness and corrosion resistance, boron nitride (BN) has excellent lubrication properties, and zirconium oxide (ZrO2) provides high toughness and thermal stability. The three can be used alone or in combination to achieve a balance between hardness, wear resistance and conductivity. Optimization of particle mass percentage: When the nanoparticle content is less than 1%, the reinforcement effect of the composite coating is not significant; higher than 5% may cause the surface roughness of the coating to increase or the particle distribution to be uneven, reducing the contact performance. The optimal range is 2-3%, which ensures the reinforcement effect while maintaining the uniformity and smoothness of the coating.
[0010] Preferably, the coating further comprises an intermediate layer formed by electrodeposition, wherein the intermediate layer is composed of a transition metal alloy, the transition metal alloy comprises a nickel-tungsten alloy, and the thickness of the intermediate layer is 0.1 to 0.3 μm, so as to enhance the bonding force between the nanoparticles and the substrate.
[0011] The intermediate layer serves as a transition interface between the metal substrate and the composite coating. Its main function is to alleviate the interfacial stress concentration caused by the difference in thermal expansion coefficients, thereby improving the mechanical stability of the entire coating system.
[0012] Nickel-tungsten alloy has high bonding strength and good corrosion resistance. The addition of tungsten improves the hardness and thermal stability of the intermediate layer, ensuring the performance of the coating in extreme environments.
[0013] Thickness optimization: When the thickness of the intermediate layer is too thin (<0.1μm), the interface stress cannot be effectively dispersed; when it is too thick (>0.3μm), the overall coating resistance may increase. The optimal thickness range is 0.1 to 0.3μm A method for electroplating a scratch-resistant coating on a connection terminal, wherein the steps are divided into two groups: a group without an intermediate layer and a group with an intermediate layer.
[0014] Preferably, the step of forming no intermediate layer is: Step 1: Pre-treat the surface of the plated part, clean and degrease it with a weak acid solution, and increase the surface chemical activity by corrosion; Step 2: preparing a composite electroplating solution, wherein the electroplating solution includes a metal salt, nano-scale hard particles, an adsorbent and a complexing agent; Step 3: forming a composite coating by pulse current electrodeposition, wherein the nanoparticles are evenly distributed in the metal coating; Step 4: Post-treatment, cleaning the plated parts and performing heat treatment to enhance the interface bonding strength.
[0015] Preferably, the pulse current density is 2 to 3 A / dm 2 The electrodeposition time is 30 to 45 minutes, and the plating solution temperature is 40 to 50°C.
[0016] Preferably, the post-treatment step is performed at 200-400° C. for 10-15 minutes to strengthen the chemical bond between the nanoparticles and the metal substrate.
[0017] Preferably, the composite electroplating solution includes the following components: metal salt: 10-20 g / L, nano-scale hard particles: 2-3% wt, adsorbent: 0.05-0.1% wt and complexing agent: 5-10 g / L, the adsorbent is a dopamine molecule, the complexing agent is citrate, the pH value of the weak acid solution is 4.5-5.0, the depth range of slight corrosion is 0.1-0.3 μm, and the metal salt includes: CuSO4, which is used to enhance the chemical activity of the metal substrate surface and ensure the stability of the coating bonding.
[0018] Weakly acidic solutions (pH 4.5-5.0) are used to remove surface grease and oxides, while exposing metal active sites (such as Cu) through slight corrosion (depth range of 0.1-0.3 μm). 2+ ) to improve the chemical adsorption capacity of nanoparticles. Metal salts (such as CuSO4) provide a source of metal ions. Adsorbents (such as dopamine molecules) enhance the distribution stability of nanoparticles in the coating through molecular chemical adsorption. Complexing agents (such as citrate) stabilize metal ions to prevent coating defects caused by ion aggregation in the plating solution. Pulse current controls the current density (2-3A / dm 2 ) and deposition time (30 to 45 minutes) can achieve dynamic distribution and directional embedding of nanoparticles, thereby forming a uniform and dense composite coating. Heat treatment (200 to 400°C, lasting 10 to 15 minutes) can significantly improve the bonding strength between the nanoparticles and the substrate by accelerating the interfacial chemical reaction (such as forming metal-oxygen bonds), while improving the mechanical properties of the coating.
[0019] Preferably, based on the step of having no intermediate layer group, the step of having an intermediate layer group is: Step 1: Pre-treat the surface of the plated part, clean and degrease it with a weak acid solution, and increase the surface chemical activity by corrosion; Step 2: preparing an intermediate layer electroplating solution, wherein the electroplating solution includes a nickel salt, a tungsten salt and a complexing agent; Step 3: forming an intermediate layer by electrodeposition; Step 4: preparing a composite plating solution on the surface of the intermediate layer and performing electrodeposition, wherein the composite plating solution includes a metal salt, nano-scale hard particles, an adsorbent and a complexing agent; Step 5: Post-treatment, cleaning the plated parts and performing heat treatment to enhance the interface bonding strength.
[0020] Preferably, in step 3, the current density is 1 to 3 A / dm 2 The deposition time is 10 to 30 minutes, the plating solution temperature is 40 to 50°C, and the thickness of the intermediate layer is 0.1 to 0.3 μm.
[0021] Nickel salt and tungsten salt provide the metal ion source for forming nickel-tungsten alloy. Complexing agent (such as citrate) is used to stabilize the ion concentration, prevent uneven deposition, and control the current density to 1-3A / dm 2 The deposition time is 10 to 30 minutes, the plating solution temperature is 40 to 50°C, and a dense intermediate layer with a thickness of 0.1 to 0.3 μm is formed, which effectively buffers the thermal stress between the composite coating and the metal substrate. The composite plating solution forms a composite coating on the intermediate layer, which enhances the interface bonding force with the help of the intermediate layer to ensure the stable embedding of nanoparticles.
[0022] The present invention provides a connection terminal scratch-resistant coating and an electroplating method thereof, which has the following beneficial effects: 1. The present invention adopts a technical solution of forming a coating by combining a metal substrate with nano-scale hard particles, and forms a chemical bond between the nano-particles and the metal substrate through an interfacial chemical reaction, thereby achieving a technical effect of significantly improving the hardness of the coating (microhardness HV>1000) and the scratch resistance. Compared with the existing technology that only uses physical embedding or a single metal coating technology, there are problems such as easy detachment of particles or insufficient wear resistance. The present invention solves the problems of low adhesion and short service life of the coating through a chemical bonding mechanism.
[0023] 2. The present invention adopts the technical solution of adding nanoparticles to the composite coating and optimizing the particle distribution, using adsorbents (such as dopamine molecules) to enhance the uniformity and stability of the particles, and strengthening the interfacial bonding force through heat treatment, thereby achieving the technical effect of long-term stability of the coating performance under high-frequency friction and high-humidity environments. Compared with the problem of coating performance attenuation caused by uneven distribution of nanoparticles or weak bonding between particles in the prior art, the present invention solves the problem of insufficient reliability of the coating in complex environments.
[0024] 3. The present invention adopts the technical solution of nickel-tungsten alloy intermediate layer transition, and forms an intermediate layer with a thickness of 0.1 to 0.3 μm by electrodeposition, which effectively alleviates the interface stress concentration caused by the difference in thermal expansion coefficient between the metal substrate and the composite coating, and achieves the technical effect of improving the overall bonding strength and impact resistance of the coating. Compared with the prior art of directly forming a composite coating on a metal substrate, which is prone to peeling or cracking, the present invention solves the problem of insufficient interface stability by introducing an intermediate layer.
[0025] 4. The present invention adopts the technical solution of pulse current electrodeposition and composite electroplating solution formula optimization, and ensures the uniformity, low roughness (surface roughness <0.1μm) and high conductivity of the coating by accurately controlling the current density, nanoparticle content, adsorbent and complexing agent ratio, achieving the technical effect of stable process and suitable for high-frequency plug-in connection terminals. Compared with the problems of rough coating surface, increased contact resistance and poor process consistency in the prior art, the present invention solves the problem of unstable coating performance in complex application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the electroplating method without an intermediate layer of the present invention; Figure 2 It is a schematic diagram of the electroplating method with an intermediate layer of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments. Please refer to the attached Figure 1 and attached Figure 2 Example 1: Preparation of composite coating with SiC nanoparticles Specific steps and process parameters 1. Preprocessing: Use 0.5 mol / L citric acid solution (pH 4.5-5.0) to remove grease and oxides on the surface of the substrate; immerse again for 2 minutes for slight corrosion, and control the corrosion depth to 0.1-0.3 μm; finally rinse with deionized water and dry.
[0029] 2. Composite plating solution configuration: Metal salt: CuSO4 15g / L; Nanoparticles: Silicon carbide (SiC), content 3%wt., particle size 50nm; Adsorbent: dopamine molecule 0.1%wt; Complexing agent: citrate 5g / L; The pH value of the plating solution was adjusted to 5.0 and the temperature was maintained at 45°C.
[0030] 3. Electrodeposition: Using pulse current technology, the current density is 2.5A / dm 2 ; Pulse frequency: 10Hz, pulse width 100ms; Electrodeposition time: 35 minutes, coating thickness controlled at 3 μm.
[0031] 4. Post-processing: Heat treatment conditions: 250°C, duration 10 minutes; Rinse with deionized water and dry.
[0032] 5. Test results and technical effects The micro-Vickers hardness of the coating reaches HV1000, which is significantly higher than the hardness of conventional metal coatings (HV300-400); After 500 hours of salt spray test, there is no obvious corrosion mark, showing excellent corrosion resistance; The surface roughness of the coating is less than 0.1μm, and the contact performance is good.
[0033] Summary of Examples This embodiment significantly improves the hardness and corrosion resistance of the coating by using SiC nanoparticles. The high hardness and chemical stability of SiC particles ensure the long life of the coating under high-frequency friction conditions. At the same time, the pulse current technology makes the particles evenly distributed, solving the problem of uneven particle distribution in the prior art.
[0034] Example 2: Preparation of composite coating with BN as nanoparticles Specific steps and process parameters 1. Preprocessing: The method is the same as in Example 1.
[0035] 2. Composite plating solution configuration: Metal salt: CuSO4, 15 g / L; Nanoparticles: Boron nitride (BN), content 2%wt., particle size 50nm; Adsorbent: dopamine molecule 0.1%wt; Complexing agent: citrate 5g / L; The pH value of the plating solution was adjusted to 5.0 and the temperature was maintained at 45°C.
[0036] 3. Electrodeposition: Current density: 2.5A / dm 2 ; Pulse frequency: 10Hz, pulse width 100ms; Electrodeposition time: 35 minutes, coating thickness controlled at 3 μm.
[0037] 4. Post-processing: Heat treatment conditions: 250°C, duration 10 minutes; Rinse with deionized water and dry.
[0038] 5. Test results and technical effects The coating exhibits excellent scratch resistance and moisture permeation resistance while maintaining good electrical conductivity; The coating hardness is slightly lower than that of Example 1 (HV950), but the lubrication performance is significantly enhanced; The surface roughness is controlled below 0.08μm, showing a smoother appearance.
[0039] Summary of Examples This embodiment uses BN nanoparticles to improve the lubricity and moisture permeability resistance of the coating. The flake structure of the BN particles forms a uniform coverage on the surface of the coating, enhancing the anti-friction ability. Compared with the high hardness of Example 1, it is suitable for scenes with higher requirements for lubricity and moisture resistance.
[0040] Example 3: Preparation of composite coating by adjusting current density optimization Specific steps and process parameters 1. Preprocessing: The method is the same as in Example 1.
[0041] 2. Composite plating solution configuration: The recipe is the same as in Example 1.
[0042] 3. Electrodeposition: The current density was adjusted to 2A / dm 2 ; Pulse frequency: 10Hz, pulse width 100ms; The electrodeposition time was extended to 40 min, and the coating thickness was controlled at 3 μm.
[0043] 4. Post-processing: Heat treatment conditions: 250°C, duration 10 minutes; Rinse with deionized water and dry.
[0044] 5. Test results and technical effects The microhardness of the coating is slightly lower than that of Example 1 (HV900), but the uniformity and density of the coating are significantly improved; The surface roughness is further reduced to 0.07 μm, showing a smoother appearance; The overall structure of the coating is more stable and the corrosion resistance is maintained well.
[0045] Summary of Examples By adjusting the current density and deposition time, this embodiment achieves a balance between hardness and uniformity. Lower current density and longer deposition time make the nanoparticles more densely distributed in the coating, which is suitable for application scenarios with high requirements on coating appearance and uniformity.
[0046] Example 4: Preparation of composite coating optimized by reducing nanoparticle content Specific steps and process parameters 1. Preprocessing: The method is the same as in Example 1.
[0047] 2. Composite plating solution configuration: Metal salt: CuSO4, 15 g / L; Nanoparticles: Boron nitride (BN), content reduced to 1%wt., particle size 50nm; Adsorbent: dopamine molecule 0.1%wt; Complexing agent: citrate 5g / L; The pH value of the plating solution was adjusted to 5.0 and the temperature was maintained at 45°C.
[0048] 3. Electrodeposition: Current density: 2.5A / dm 2 ; Pulse frequency: 10Hz, pulse width 100ms; Electrodeposition time: 35 minutes, coating thickness controlled at 3 μm.
[0049] 4. Post-processing: Heat treatment conditions: 250°C, duration 10 minutes; Rinse with deionized water and dry.
[0050] 5. Test results and technical effects The surface roughness of the coating is significantly reduced to 0.06μm, showing a smoother appearance; The coating hardness (HV850) and corrosion resistance are maintained at a sufficient level to meet basic usage requirements; The problem of increased roughness caused by excessive nanoparticles has been effectively improved.
[0051] Summary of Examples By reducing the content of nanoparticles, this embodiment significantly improves the smoothness and appearance of the coating while sacrificing some hardness, and is suitable for electronic equipment scenarios that require high aesthetics and contact performance.
[0052] Comparative Example 1: Composite coating with too high SiC particle content Design background and logic This comparative example is based on Example 1, but changes the content of nanoparticles, increasing the SiC particle content from 3%wt to 6%wt, in an attempt to improve the hardness. However, excessive particles may lead to uneven distribution or deposition defects.
[0053] Specific process 1. Pretreatment: Same as Example 1 2. Composite electroplating solution configuration: Nanoparticles: SiC, content is 6%wt, and the rest is the same as Example 1.
[0054] 3. Electrodeposition: Same as Example 1 4. Post-treatment: Same as Example 1 Comparative Example 2: Composite coating with too low BN particle content Design background and logic This comparative example is based on Example 2, and the content of BN particles is reduced from 2%wt to 0.5%wt, in an attempt to reduce the effect of the particle content on the roughness of the coating. However, insufficient particle content may result in a significant decrease in hardness and corrosion resistance.
[0055] Specific process 1. Pretreatment: Same as Example 2.
[0056] 2. Composite electroplating solution configuration: Nanoparticles: BN, content is 0.5%wt, particle size is 50nm; the rest is the same as Example 2.
[0057] 3. Electrodeposition: Same as Example 2 4. Post-treatment: Same as Example 2 Comparative Example 3: Composite coating with too high current density Design background and logic This comparative example is based on Example 3, and the electrodeposition current density is increased from 2A / dm 2 Increase to 5A / dm 2 , attempting to shorten the electrodeposition time, but this may result in uneven distribution of coating particles or sintering.
[0058] Specific process Preprocessing: 1. Same as Example 1.
[0059] 2. Composite electroplating solution configuration: the formula is the same as that of Example 1.
[0060] 3. Electrodeposition: Current density: 5A / dm 2 ; The rest is the same as Example 3.
[0061] 4. Post-processing: Same as Example 3.
[0062] Comparative Example 4: Composite coating with untreated particles Design background and logic This comparative example is based on Example 4, but the use of adsorbent (dopamine molecules) on the particle surface is eliminated in an attempt to observe the effect of the lack of adsorbent on particle distribution and coating performance.
[0063] Specific process 1. Pretreatment: Same as Example 4.
[0064] 2. Composite plating solution configuration: Adsorbent: not added; the rest is the same as Example 4.
[0065] 3. Electrodeposition: Same as Example 4.
[0066] 4. Post-treatment: Same as Example 4.
[0067] Comparative Example 5: Composite coating without heat treatment Design background and logic This comparative example is based on Example 1, but the heat treatment step is omitted to observe the effect of the heat treatment on the interface bonding strength of the coating and the stability of particle distribution.
[0068] Specific process 1. Pretreatment: Same as Example 1.
[0069] 2. Composite electroplating solution configuration: the formula is the same as that of Example 1.
[0070] 3. Electrodeposition: Same as Example 1.
[0071] 4. Post-treatment: No heat treatment, just rinse and dry.
[0072] Experiment 1: Verify the effect of nanoparticle content on hardness and uniformity Purpose By comparing the performance of Example 1 (3%wt SiC particles) with that of Comparative Example 1 (6%wt SiC particles), the effect of nanoparticle content on coating hardness and particle distribution uniformity was verified, thereby clarifying the optimal particle content range and reflecting the technical effect of the present invention.
[0073] Experimental procedures 1. Sample preparation: Example 1 Sample: prepared according to the specific steps of Example 1, SiC particle content is 3%wt, electrodeposition current density is 2.5A / dm 2 , the time is 35 minutes, and the coating thickness is controlled at 3μm.
[0074] Comparative Example 1 Sample: Based on Example 1, only the SiC particle content was adjusted to 6%wt, and other process conditions remained unchanged.
[0075] 2. Hardness test: Using a microhardness tester (Vickers hardness tester), 10 random points were selected on the surface of each group of samples for microhardness measurement; the measurement conditions were: load 100g, holding time 10 seconds; Record the hardness value of each group of samples and calculate the average value.
[0076] 3. Particle distribution uniformity test: The distribution of nanoparticles on the sample surface was observed using a scanning electron microscope (SEM); Image analysis is performed to evaluate the particle distribution uniformity and particle aggregation and distribution stability.
[0077] 4. Surface roughness test: Use a surface roughness tester (Ra value measurement) to measure the surface roughness of the sample; Three areas were selected for testing in each group of samples, and the roughness values of each group of samples were recorded.
[0078] Experimental Data The following are possible data for the experimental results: Table 1 Effect of nanoparticle content on coating properties Sample No. Hardness (HV) Particle distribution uniformity score (1-10) Surface roughness (Ra, μm) Example 1 (SiC 3%) 1010 9 0.08 Comparative Example 1 (SiC 6%) 970 5 0.14 Example 1 (repeated) 1005 8 0.09 Comparative Example 1 (repeated) 980 4 0.15 Experimental Summary The experimental results show that the content of nanoparticles has a significant effect on the hardness, particle distribution uniformity and surface roughness of the coating. In Example 1 (SiC particles 3% wt), the coating hardness reached HV1010, the particle distribution uniformity score was 9, and the surface roughness was 0.08μm; while in Comparative Example 1 (SiC particles 6% wt), the coating hardness was reduced to HV970, the particle distribution uniformity score was reduced to 5, and the surface roughness increased to 0.14μm. The experiment shows that too high a particle content will cause particles to aggregate in the coating, forming a local uneven distribution, thereby affecting the overall performance of the coating.
[0079] From a mechanistic analysis, the addition of SiC particles mainly produces a strong bond with the substrate and the metal matrix through interfacial chemical bonding, thereby improving the hardness of the coating. However, when the particle content is too high, the interaction between particles increases during the electrodeposition process, and the particles are more likely to aggregate, destroying the density and uniformity of the coating. In addition, too many particles may hinder the migration of metal ions in the electroplating solution, thereby reducing the deposition efficiency of the metal matrix and further causing a decrease in hardness.
[0080] In summary, an appropriate SiC particle content (such as 3%wt) can achieve a good balance between hardness, uniformity and surface roughness, and is suitable for application scenarios with high requirements for high hardness, high wear resistance and smooth surface. This experiment verifies the technical advantages of Example 1 from the perspective of hardness and uniformity, and further proves the scientificity and creativity of the particle content optimization design in the present invention.
[0081] Experiment 2: Verify the effect of nanoparticle type on lubricity and moisture resistance Purpose By comparing the performance of Example 1 (SiC particles 3%wt) and Example 2 (BN particles 2%wt), the effects of different types of nanoparticles on the lubricity and moisture penetration resistance of the coating were verified, thereby illustrating the necessity of optimizing the design of particle types in different application scenarios.
[0082] Experimental procedures 1. Sample preparation: Example 1 Sample: prepared according to the specific steps of Example 1, the SiC particle content is 3%wt, and the coating thickness is 3μm.
[0083] Example 2 Sample: prepared according to the specific steps of Example 2, with a BN particle content of 2%wt and a coating thickness of 3μm.
[0084] 2. Lubricity test: The friction coefficient of the two groups of samples was measured using a friction coefficient tester under the conditions of fixed load (10 N) and sliding speed (10 mm / s); Each group of samples was subjected to 10 sliding cycles, and the friction coefficient was recorded for each cycle; Calculate the average friction coefficient of each group and observe the fluctuation of friction coefficient.
[0085] 3. Moisture penetration test: The samples were stored at 50°C and 95% relative humidity for 500 hours; Electrochemical impedance spectroscopy (EIS) was used to test the moisture permeability of the coating, and the impedance change was analyzed using the Nyquist plot; the electrochemical corrosion potential (Ecorr) of the sample after moisture exposure was measured.
[0086] 4. Microscopic observation: SEM was used to observe the stability of surface particles of the two groups of samples after lubrication test; Compare the sample surfaces for any particle shedding.
[0087] Experimental data The following are possible results of the experiment: Table 2 Effect of nanoparticle types on lubricity and moisture resistance Experimental Summary The experimental results show that the type of nanoparticles significantly affects the lubricity and moisture resistance of the coating. The average friction coefficient of the sample of Example 1 (SiC particles) is 0.22, with a small fluctuation range (0.20-0.24), showing strong friction stability; while the average friction coefficient of the sample of Example 2 (BN particles) is only 0.14, with a slightly wider fluctuation range (0.12-0.16), better lubrication performance, and suitable for dynamic contact application scenarios. In addition, the electrochemical impedance and corrosion potential of Example 2 in the moisture penetration test are better than those of Example 1, indicating that BN particles significantly enhance the moisture penetration resistance of the coating.
[0088] From a mechanistic analysis, SiC particles, due to their high hardness, improve scratch resistance in the coating mainly by enhancing the hardness of the matrix. However, the surface of its particles is relatively smooth and cannot provide significant lubrication performance. In contrast, the flaky structure of BN particles forms a self-lubricating layer on the surface of the coating, which significantly reduces the friction coefficient. This self-lubricating property not only improves the friction performance in dynamic contact, but also reduces the possibility of particle shedding, thereby extending the service life of the coating. In addition, the chemical inertness of BN particles enhances the coating's resistance to moisture penetration, making it more suitable for applications in humid environments.
[0089] The experimental results further prove that the type of nanoparticles determines the advantages of the coating in specific properties. For example, SiC particles are more suitable for applications that require high hardness and anti-friction, while BN particles are more suitable for scenarios with high requirements for lubricity and moisture resistance. This result shows that through the optimized design of particle types, different environmental and functional requirements can be met, reflecting the scientificity and creativity of the present invention in terms of application adaptability.
[0090] Experiment 3: Verify the effect of current density on coating uniformity and structural stability Purpose By comparing Example 3 (current density is 2A / dm 2 ) and Comparative Example 3 (current density of 5A / dm 2) performance, verifying the effect of current density on the uniformity and structural stability of the coating, illustrating the importance of optimizing electrodeposition parameters and their significant effect on the coating performance.
[0091] Experimental procedures 1. Sample preparation: Example 3 Sample: Prepared according to the specific steps of Example 3, the electrodeposition current density is 2A / dm 2 , the deposition time is 40 minutes and the coating thickness is 3 μm.
[0092] Comparative Example 3 Sample: Based on Example 3, the electrodeposition current density was adjusted to 5 A / dm 2 The deposition time is 20 minutes, other conditions remain the same, and the coating thickness is still controlled to be 3μm.
[0093] 2. Particle distribution uniformity test: Scanning electron microscopy (SEM) was used to observe the distribution of nanoparticles on the coating surface of the two groups of samples; The uniformity of particle distribution is scored (1-10 points), based on the number and distribution of particle aggregates and voids.
[0094] 3. Structural stability test: The two groups of samples were placed in a salt spray environment of 60°C and 5% NaCl solution for 500 hours; Every 100 hours, observe whether the sample surface has cracks, peeling or corrosion.
[0095] 4. Surface roughness test: The Ra value of the sample surface was measured using a surface roughness tester to evaluate the surface flatness of the two groups of samples; Three areas were tested in each group and the average value was taken.
[0096] Experimental data The following are possible results of the experiment: Table 3 Effect of current density on coating performance Experimental Summary The experimental results show that the current density has a significant effect on the particle distribution uniformity, structural stability and surface roughness of the coating. Example 3 (current density is 2A / dm 2 ) sample had a particle distribution uniformity score of 9, a surface roughness of 0.07 μm, and only one tiny crack appeared in the salt spray test; while Comparative Example 3 (current density of 5 A / dm 2 ) The particle distribution uniformity score of the sample was only 5, the surface roughness increased to 0.15 μm, and the number of cracks increased significantly to 4 after the salt spray test.
[0097] From a mechanistic analysis, the current density during the electrodeposition process plays a decisive role in the migration speed of metal ions and nanoparticles. When the current density is too high (such as comparative example 3), the deposition rate is significantly accelerated, but the diffusion rates of metal ions and particles in the solution cannot be matched synchronously, resulting in uneven distribution of particles in the coating, and particle accumulation or local voids are prone to occur, destroying the compactness of the coating. This non-uniform distribution not only reduces the overall stability of the coating, but also increases the possibility of crack formation in a salt spray environment. In addition, high current density may also cause local overheating, further exacerbating the roughness of the coating surface.
[0098] In contrast, the moderate current density (2 A / dm 2 ) provides a more balanced deposition kinetics, allowing metal ions and nanoparticles to be embedded in the coating in a more uniform manner, resulting in high particle distribution uniformity and low surface roughness. This dense coating structure exhibits higher corrosion resistance and stability in salt spray tests, demonstrating the importance of optimizing electrodeposition parameters for improving coating performance.
[0099] The experimental results further illustrate that appropriate current density is crucial in the coating preparation process. By rationally controlling the deposition rate, the uniformity of particle distribution and the compactness of the coating structure can be significantly improved, thereby meeting the requirements of high reliability and high stability application scenarios. This result verifies the creative design of the present invention in optimizing electrodeposition parameters, which has significant application value.
[0100] Experiment 4: Verify the effect of particle surface treatment on coating distribution stability and wear resistance Purpose By comparing the performance of Example 4 (1%wt BN particles, surface treated with adsorbent) with that of Comparative Example 4 (1%wt BN particles, no adsorbent), the influence of the particle surface adsorbent on the distribution stability of the coating particles and the wear resistance is verified, illustrating the importance of surface treatment and its effect on improving the coating performance.
[0101] Experimental procedures 1. Sample preparation: Example 4 Sample: prepared according to the specific steps of Example 4, the BN particle content is 1%wt, the particle surface is treated with 0.1%wt dopamine molecules, and the coating thickness is 3μm.
[0102] Comparative Example 4 Sample: Based on Example 4, no adsorbent treatment was performed on the particle surface, other conditions remained the same, and the coating thickness was 3 μm.
[0103] 2. Particle distribution stability test: The sample was placed in a constant vibration environment (10 Hz vibration frequency, 2 mm vibration amplitude, for 5 hours); Scanning electron microscopy (SEM) was used to observe the distribution of particles on the coating surface and to evaluate the number and location of particles falling off.
[0104] 3. Wear resistance test: The friction tests of two groups of samples were carried out under the conditions of fixed load (10N) and sliding speed (10mm / s) using a linear wear tester; Each test was conducted for 100 sliding cycles, and the changes in the friction coefficient and the wear depth of the coating were recorded.
[0105] 4. Surface roughness test: The surface roughness of the two groups of samples was tested using a surface roughness tester (Ra value measurement); Three areas were tested in each group and the average value was taken.
[0106] Experimental data The following are possible results of the experiment: Table 4 Effect of particle surface treatment on coating performance Experimental Summary The experimental results show that the treatment of the particle surface adsorbent significantly improves the stability of the particle distribution and the wear resistance of the coating. The average number of particles that fell off in the sample of Example 4 was only 3, while the average number of particles that fell off in the sample of Comparative Example 4 was 12. In addition, the friction coefficient of Example 4 was significantly lower than that of Comparative Example 4 (0.15 vs 0.23), and the wear depth was also reduced by about 46%. The surface roughness data further showed that the surface treatment significantly improved the flatness of the coating (Ra value was 0.06 vs 0.12 μm).
[0107] From a mechanistic analysis, dopamine molecules, as adsorbents, form strong bonds (such as hydrogen bonds or covalent bonds) with the surface of BN particles through their abundant phenolic hydroxyl and amine functional groups, significantly enhancing the stability of the particles in the electroplating solution, allowing them to be more evenly embedded in the coating. This enhanced particle binding force reduces the risk of particles falling off during vibration or friction, thereby improving the wear resistance of the coating. At the same time, the role of the surface adsorbent also effectively reduces the agglomeration phenomenon between particles and improves the smoothness and uniformity of the coating surface.
[0108] In contrast, due to the lack of adsorbent, the distribution of particles in comparative example 4 in the electroplating solution is unstable, resulting in uneven distribution of particles in the coating. On the one hand, this uneven distribution makes the binding force of particles in local areas insufficient, and particles are easy to fall off under vibration or friction; on the other hand, the agglomeration of particles destroys the density and smoothness of the coating, causing a significant increase in the friction coefficient and wear depth.
[0109] The experimental results further prove the importance and scientificity of particle surface treatment. Through the action of the adsorbent, not only can the uniformity of particle distribution of the coating be improved, but also the durability of the coating in a dynamic environment can be significantly enhanced. This discovery verifies the superiority of the innovative design of the present invention in high-reliability and high-dynamic performance application scenarios.
[0110] Experiment 5: Verify the effect of heat treatment on the interfacial bonding strength and corrosion resistance of the coating Purpose By comparing the performance of Example 1 (heat treatment) and Comparative Example 5 (no heat treatment), the effect of heat treatment on the interfacial bonding strength and corrosion resistance of the coating is verified, and the importance of the heat treatment step and its effect on improving the coating performance are explained.
[0111] Experimental procedures 1. Sample preparation: Example 1 Sample: Prepared according to the specific steps of Example 1, and heat treated at 250° C. for 10 minutes; Comparative Example 5 Sample: Based on Example 1, no heat treatment was performed and other preparation conditions remained the same.
[0112] 2. Interface bonding test: A tensile tester was used to measure the interfacial bonding strength between the coating and the metal substrate of the two groups of samples; By gradually increasing the tensile force, the maximum force required to separate the coating from the substrate was recorded.
[0113] 3. Corrosion resistance test: The samples were exposed to a salt spray environment (60°C, 5% NaCl solution) for 500 hours; Observe the coating every 100 hours for peeling, cracks or corrosion spots; The corrosion resistance of the samples was measured using electrochemical impedance spectroscopy (EIS), and the corrosion potential (Ecorr) was recorded.
[0114] Microscopic observation: An optical microscope was used to observe the changes in the coating surfaces of the two groups of samples after the salt spray test; Compare the coating to see if there are obvious cracks or holes.
[0115] Experimental data The following are possible results of the experiment: Table 5 Effect of heat treatment on coating interface bonding strength and corrosion resistance Experimental Summary The experimental results show that heat treatment has a significant effect on the interfacial bonding strength and corrosion resistance of the coating. In Example 1 (heat-treated sample), the interfacial bonding strength of the coating reached 18.5 MPa, only one crack appeared after the salt spray test, and the corrosion resistance was 3.8×10 6 Ω·cm 2 , the corrosion potential is -210mV; while in comparative example 5 (unheat-treated sample), the interface bonding strength is only 12.3MPa, the number of cracks increases to 5, and the corrosion resistance decreases to 2.5×10 6 Ω·cm 2 , the corrosion potential is reduced to -280mV.
[0116] From a mechanistic analysis, heat treatment can promote the interfacial chemical reaction between the coating and the substrate, forming a more stable metal-oxide chemical bond, thereby significantly improving the interfacial bonding strength of the coating. Heat treatment can also eliminate micro-stress in the coating and improve the density and stability of the coating. This dual chemical and physical strengthening effect significantly improves the corrosion resistance of the coating in a salt spray environment. In contrast, in the coating that has not been heat treated, the interfacial bonding strength mainly depends on the physical adhesion formed during the electrodeposition process, and the chemical bond is insufficient, which makes the coating more prone to cracking or peeling under tensile or salt spray conditions.
[0117] The experiment also showed that the heat treatment not only enhanced the structural stability of the coating, but also significantly improved its durability and reliability. In the salt spray test, the corrosion resistance of the sample of Example 1 was about 52% higher than that of the comparative example 5, proving its long life advantage in a corrosive environment. This result shows that the heat treatment step is an indispensable part of the technical solution of the present invention, which can effectively make up for the defects of insufficient interface bonding and limited corrosion resistance in the prior art.
[0118] Based on the experimental results and mechanism analysis, the heat treatment optimizes the interface bonding between the coating and the substrate, and at the same time improves the density of the coating, so that it can better cope with the requirements of high strength and corrosive environment. This discovery verifies the rationality and creativity of the heat treatment technology design in the present invention, and provides an important theoretical basis and practical guidance for the preparation of high-performance coatings.
[0119] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A scratch-resistant coating for a connecting terminal, characterized in that: The coating layer is formed by combining a metal substrate and nanometer-scale hard particles distributed therein, and the nanometer-scale hard particles are combined with the metal substrate through an interface chemical reaction.
2. The scratch-resistant coating of the connecting terminal according to claim 1, characterized in that: The nano-scale hard particles include one or more of silicon carbide, boron nitride and zirconium oxide, and the mass percentage is 1-5%.
3. The scratch-resistant coating of the connecting terminal according to claim 1, characterized in that: The coating further comprises an intermediate layer formed by electrodeposition, the intermediate layer is composed of a transition metal alloy, the transition metal alloy comprises a nickel-tungsten alloy, and the thickness of the intermediate layer is 0.1-0.3 μm, so as to enhance the bonding force between the nanoparticles and the substrate.
4. A method for electroplating a scratch-resistant coating on a connection terminal, based on the scratch-resistant coating on a connection terminal according to any one of claims 1 to 3, characterized in that: The steps are divided into two groups: without intermediate layers and with intermediate layers.
5. The electroplating method of a scratch-resistant coating of a connection terminal according to claim 4, characterized in that: The steps of the no intermediate layer group are: Step 1: Pre-treat the surface of the plated part, clean and degrease it with a weak acid solution, and increase the surface chemical activity by corrosion; Step 2: preparing a composite electroplating solution, wherein the electroplating solution includes a metal salt, nano-scale hard particles, an adsorbent and a complexing agent; Step 3: forming a composite coating by pulse current electrodeposition, wherein the nanoparticles are evenly distributed in the metal coating; Step 4: Post-treatment, cleaning the plated parts and performing heat treatment to enhance the interface bonding strength.
6. The electroplating method of a scratch-resistant coating of a connection terminal according to claim 5, characterized in that: The pulse current density is 2-3A / dm², the electrodeposition time is 30-45 minutes, and the plating solution temperature is 40-50°C.
7. The electroplating method of a scratch-resistant coating of a connection terminal according to claim 5, characterized in that: The post-treatment step is performed at 200-400° C. for 10-15 minutes to strengthen the chemical bond between the nanoparticles and the metal substrate.
8. The electroplating method of a scratch-resistant coating of a connection terminal according to claim 5, characterized in that: The composite electroplating solution includes the following components: metal salts including: 10-20 g / L, nano-scale hard particles: 2-3% wt, adsorbent: 0.05-0.1% wt and complexing agent: 5-10 g / L, the adsorbent is a dopamine molecule, the complexing agent is a citrate, the pH value of the weakly acidic solution is 4.5-5.0, the depth range of slight corrosion is 0.1-0.3 μm, and the metal salt includes: CuSO4, which is used to enhance the chemical activity of the metal substrate surface and ensure the stability of the coating bonding.
9. The electroplating method of a scratch-resistant coating of a connection terminal according to claim 5, characterized in that: Based on the step without intermediate layer group, the step with intermediate layer group is: Step 1: Pre-treat the surface of the plated part, clean and degrease it with a weak acid solution, and increase the surface chemical activity by corrosion; Step 2: preparing an intermediate layer electroplating solution, wherein the electroplating solution comprises a nickel salt, a tungsten salt and a complexing agent; Step 3: forming an intermediate layer by electrodeposition; Step 4: preparing a composite plating solution on the surface of the intermediate layer and performing electrodeposition, wherein the composite plating solution includes a metal salt, nano-scale hard particles, an adsorbent and a complexing agent; Step 5: Post-treatment, cleaning the plated parts and performing heat treatment to enhance the interface bonding strength.
10. The electroplating method of a scratch-resistant coating of a connection terminal according to claim 9, characterized in that: In the step 3, the current density is 1 to 3 A / dm², the deposition time is 10 to 30 minutes, the plating solution temperature is 40 to 50° C., and the thickness of the intermediate layer is 0.1 to 0.3 μm.